The Impact Of Interaktive Role Playing On Efl Learners’ Willingness To Speak - Emilizar Emilizar; Sylvia Sylvia (Departement of Mathematics Education, 2025)
The speaking ability of the majority of grade VII students at MTsN 3 Padang Pariaman are still seen in the teaching and learning process in the classroom, students tend to be passive, hesitant, nervous, embarrassed and less active in expressing their thoughts through good communication in otherwise lack of speaking skills. Therefore, teachers must efforts to develop their creativity in teaching, one of which is choosing the right and optimal learning method to achieve good learning objectives, namely using the Role Playing learning method. This study aims to determine the effect of the role playing method on improving students' speaking skills in English subjects. This research was done at MTsN 3 Padang Pariaman in the odd semester of 2024/2025. The research method uses a quantitative approach in the shape of an experiment of the CAR (classroom Action Research) type. The population is all students of class VII.1 with consist of 32 students as a sample for the study. The techniques of data collection used are observation, interview, test and documentation methods. The technique of data analysis used is descriptive analysis which is using the dependent